Bioacoustics and systematics of Mecopoda (and related forms) from South East Asia and adjacent areas (Orthoptera, Tettigonioidea, Mecopodinae) including some chromosome data - Heller, Klaus-Gerhard; Baker, Ed; Ingrisch, Sigfrid; Korsunovskaya, Olga; Liu, Chun-Xiang; Riede, Klaus; Warchałowska-Šliwa, Elżbieta (Zootaxa, 2021)
Bush-crickets (or katydids) of the genus Mecopoda are relatively large insects well-known for their sounds for centuries. Bioacoustic studies in India and China revealed a surprisingly large diversity of sound patterns. We extend these studies into the tropics of South East Asia using integrative taxonomy, combining song analysis, morphology of sound producing organs and male genitalia as well as chromosomes, to get a better understanding of the phylogeny and evolution of this widespread group. Besides the closely related genus Eumecopoda, the genus Mecopoda contains some isolated species and a large group of species which we assign to the Mecopoda elongata group. Some species of this group have broad tegmina and stridulatory files with different tooth spacing patterns and produce continuous, often relatively complicated, trill-like songs. The species of another subgroup with narrower wings have all similar files. Their songs consist of echemes (groups of syllables) which differ in syllable number and syllable repetition rate and also in echeme repetition rate. Our results show that South East Asia harbours a large and certainly not yet fully explored number of Mecopoda species which are most easily and clearly identified by song. Based on the data, five new forms are described: Mecopoda mahindai Heller sp. nov., Mecopoda paucidens Ingrisch, Su & Heller sp. nov., Mecopoda sismondoi Heller sp. nov., Mecopoda niponensis vietnamica Heller & Korsunovskaya subsp. nov., Eumecopoda cyrtoscelis zhantievi Heller subsp. nov. In addition, some taxonomic changes are proposed: Eumecopoda Hebard, 1922 stat. rev., Paramecopoda Gorochov, 2020, syn. nov. of Eumecopoda Hebard, 1922, Mecopoda javana (Johansson, 1763) stat. nov. (neotype selected) with M. javana minahasa Gorochov, 2020 stat. nov., M. javana darevskyi Gorochov, 2020 stat. nov., M. javana buru Gorochov, 2020 stat. nov., Mecopoda macassariensis (Haan, 1843) stat. rev., Mecopoda ampla malayensis Gorochov, 2020 syn. nov., Mecopada ampla javaensis Gorochov, 2020 syn. nov., Mecopoda fallax aequatorialis Gorochov, 2020 syn. nov., the last three are all synonyms of Mecopoda himalaya Liu, 2020, Mecopoda yunnana Liu 2020, stat. nov.